Karst hydrogeology of the Canadian Rocky Mountains - Worthington, Stephen Richard Hurst (My University, 1991)
An analysis of the discharge and hydrochemical variations of contrasting springs at Crowsnest Pass showed they were part of a vertical hierarchy in the aquifer, in which underflow and overflow components play a dominant role. It was found that karst springs at Crowsnest Pass and elsewhere show a range between two end members. Thermal springs have long, deep flow paths, with high sulphate concentrations, low discharge variance and low flow velocities. Overflow springs have local shallow flow paths, low sulphate, high discharge variance, and high flow velocities. Intermediate between these end members are underflow springs; in the Rocky Mountains these are mostly aggraded, and give the sustained winter flow and high sulphate concentrations found in major rivers. It was found that underflow or overflow behaviour is able to explain most of the contrasts found between karst springs in discharge and sulphate concentrations. Conversely, differences in bicarbonate concentration are principally due to the ratio of allogenic to autogenic recharge to the aquifer. Hydraulic analysis showed that gradients decrease in the downstream direction, and are typically 0.0001-0.05 at maximum discharges, that friction factors vary by a factor of >1000, and that most active conduits have closed-channel flow and are in dynamic equilibrium with sediment supply. The analysis of the hydrological data from Crowsnest Pass and elsewhere has led to the development of a new conceptual model for groundwater flow in karst, in which the Hagen-Poiseuille flow net conditions the aquifer for conduit development, and determines where the conduits will be. The model explains why most conduits are in dynamic equilibrium with sediment supply, why temperate karst springs are mostly vauclusian, what the mean time for speleogenesis is, how >98% of the solution of limestone is in the surficial zone, and why there are karstic hot springs in the Rocky Mountains and elsewhere. The model enables predictions to be made of sink to resurgence flow velocities, of conduit depth below the water table, of the ratio of beds to joints used by conduits, of the spacing between cave tiers, and of the depth of vauclusian springs. This new understanding of how karstic aquifers develop and function gives a powerful predictive ability to karst hydrogeology.
Keywords: Geography; Geography